LITERASI KEUANGAN DAN INKLUSI KEUANGAN SISWA MADRASAH ALIYAH SUNGGUMINASA : STUDI KUALITATIF TEMATIK - Nur Biah; Muryani Arsal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine students' understanding of financial concepts, financial management practices, access to financial services, barriers to financial inclusion, and the contribution of madrasahs in improving the financial literacy and awareness of students at Madrasah Aliyah Sungguminasa. This study uses a qualitative approach with thematic analysis, involving twenty students selected through purposive sampling. Data were obtained through in-depth interviews and group discussions to explore students' perceptions, experiences, and financial behaviors comprehensively. The findings show that students have understood basic financial concepts, such as saving, distinguishing between needs and wants, and using digital wallets. However, they have not mastered advanced financial concepts, particularly investment, risk, interest, and inflation. In terms of financial management, only a small percentage of students keep track of their cash flow, indicating unplanned and inconsistent financial practices. In addition, ownership of bank accounts as a formal financial service is still minimal, but the use of digital financial services is now increasingly widespread and accessible. The main barriers to financial inclusion include lack of knowledge, limited identity documents, minimal parental guidance, and financial education that is not yet applicable. The role of madrasahs through economic education and OSIM activities is considered to have a positive impact, but their implementation is still dominated by theoretical aspects. This study emphasizes the need for continuous practice-based financial education to improve students' financial competence and engagement so that they are better prepared to face the realities of the modern economy.